Proverbs - Miller, John W., 1926- (Believers church Bible commentary., 2004)
The uniqueness of this commentary is its detailed, first-time uncovering of evidence that there were two editions of Proverbs, the first in the time of Solomon and the second created by "the men of Hezekiah" in support of King Hezekiah's historic religious reforms. Up to this time the puzzling features of the book's design, purpose, and message are clarified in this light and the book's relevance for its time and ours greatly enhanced. "Proverbs is a treasury of God's wisdom, and John W. Miller is a gifted guide to its proper interpretation. He has given the church a clear, interesting, and insightful commentary on this important biblical book."--Tremper Longman, Westmont College A part of the Believers Church Bible Commentary Series. - Publisher